Pengaruh Inokulasi Mangan Pada Besi Cor Kelabu Terhadap Kekuatan Tarik - Nugroho, Adi; , Agus Yulianto, ST., MT (2016)
This study aims to determine the effect of inoculation of manganese in gray cast iron to strength power. This study uses sand molds with cylindrical wood pattern. Methodology this study is done with cast iron melting in induction fireplace and then is poured in sand molds for making gray cast iron specimen. This research to determine the melting temperature and chemical composition C and silicon in the form of liquid gray cast iron using test equipment CE Meter then the gray cast iron specimen research the chemical composition and power strength research and then the hardness test and micro photo. The result of the research is a chart obtained from CE METER shows the temperature 1315.2 0C during tapping beginning poured into the mold. A decrease in temperature of up to 1155.2 0C, 1315.2 0 C form is a liquid metal with CEL value = 4.17%; C = 3.60%; Si = 2.24%. After the temperature 1155.20 C metal begins to freeze. The metal freeze all at temperatures 1113.20 C, on the condition of the red metal. On the results of the chemical composition contained 20 kinds, but only 6 elements which can influence on cast iron are Fe, CSi, Mn, Cr and Ni. In the picture shows the graphite microstructure, perlite and cementite, which affected the price of hardness. Power test results showed the addition of Mn got the highest of 209,81 N / mm2 and the results obtained 41.14 HRB hardness. Based on these data it can be concluded that the addition of manganese can increase the hardness and power strength. Keywords : inoculation, gray cast iron, CE meter, tensile testing, hardness